2015
DOI: 10.3390/ijerph120505373
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in the Prevalence of High Homocysteine Levels Among Low-Income Rural Kazakh and Uyghur Adults in Far Western China and Its Implications for Preventive Public Health

Abstract: Objective: Homocysteine (Hcy) is a relevant biomarker of vascular disease: serum Hcy concentrations will increase the risk of systolic hypertension, whereas hyperhomocysteinemia (HHcy) has a synergistic effect with hypertension and increases the risk of cardiovascular disease. However, information has primarily been gathered from high-income and urban settings, and little is known regarding low-income rural settings. This study focused on a low-income rural and nomadic minority residing in far western China. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
4
22
1
Order By: Relevance
“…e gender difference in HHcy is likely to be associated with sexrelated hormones, the higher phosphocreatine synthesis in males, and the higher rate of remethylation and transmethylation in females than in males [26]. In this study, similar to previous findings [25,27], the prevalence of HHcy increased with age.…”
Section: Discussionsupporting
confidence: 88%
“…e gender difference in HHcy is likely to be associated with sexrelated hormones, the higher phosphocreatine synthesis in males, and the higher rate of remethylation and transmethylation in females than in males [26]. In this study, similar to previous findings [25,27], the prevalence of HHcy increased with age.…”
Section: Discussionsupporting
confidence: 88%
“…9 These inconsistencies may be attributed to the fact that plasma Hcy levels differ by age and have significant gender and ethnic dependency. 15 The mean level of Hcy in our sample was 10.5 µmol/L, which was greater than previously reported among American population in the National Health and Nutrition Examination Survey (7.72 µmol/L) and lower than mean value reported among Chinees population (11.96 µmol/L). 16,17 In the last decade, epidemiological observations have reported that Hcy status is linked to cardiovascular disease and was suggested to be an independent predictor of cardiac death among adults.…”
Section: Multivariate Analysis For Hcy Status and Mscontrasting
confidence: 78%
“…Low folate and vitamin B12 are related with elevated homocysteine levels [11]. The incidence of homocysteine levels is altered in ethnic groups due to different genetic conditions, nutritional factors (vitamin deficiency and folic acid deficiency) and lifestyle behaviors [12]. Therefore, the present study was undertaken to examine a possible relationship between plasma homocysteine level and coronary artery disease in Indian patients.…”
mentioning
confidence: 96%